PEMBELAJARAN TEAMS GAMES TOURNAMENT CHALLENGE RELAY PADA MATERI SISTEM PERNAPASAN UNTUK MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN SOSIAL SISWA SMP - Fernanda Putri, Kamelia; Puspitarini, Sapti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning outcomes at UPT SMP Negeri 12 Gresik are still relatively low. This study aims to see the effect of Teams Games Tournament learning to improve students' learning outcomes and social skills. The method used in this study is a pre-experimental One Group Pretest-Posttest Design, where there is only one group without a control group. The data analysis technique used in this study is supported by SPSS software, namely the normality test with the Shapiro-Wilk test, the Paired Sample t-Test if the data is normally distributed and the Wilcoxon test if the data is detected to have an abnormal distribution and the N-Gain test. The results of this study are that Teams Games Tournament Challenge Relay learning is able to improve science learning outcomes and students' social skills at UPT SMP Negeri 12 Gresik.